Siccità / un produzione Wildside e Vision Distribution in collaborazione con Sky, Prime Video ; sceneggiatura, Francesca Archibugi, Paolo Giordano, Francesco Piccolo, Paolo Virzì ; prodotto da Mario Gianani, Lorenzo Gangarossa ; diretto da Paolo Virzì. - Virzì, Paolo; Archibugi, Francesca, 1960-; Giordano, Paolo, 1982-; Piccolo, Francesco, 1964-; Orlando, Silvio, 1957-; Mastandrea, Valerio; Lietti, Elena; Ragno, Tommaso, 1967-; Pandolfi, Claudia, 1974-; Marchioni, Vinicio, 1975-; Bellucci, Monica, 1968-; Bigazzi, Luca, 1958-; et al. (CG Entertainment, 2022)
"It hasn't rained in Rome for 3 years. Regulations and customs change as a group of intertwined characters deal with the water shortage." -- IMDb
Wide screen (16/9, 2.39:1).
THIS PAL REGION 2 DISC MAY NOT BE COMPATIBLE WITH ALL STANDARD PLAYERS.
Originally produced as a motion picture in 2022.
Special features: Backstage.
Keywords: Droughts -- Italy -- Rome -- Drama.; Water-supply -- Italy -- Rome -- Management -- Drama.; Rome (Italy) -- Drama.; Droughts.; Water-supply -- Management.; Italy -- Rome.; Comedy films.; Drama.; Feature films.; Video recordings for people with visual disabilities.; Video recordings for the hearing impaired.